Food security policy in Iraq and the challenges of response after 2003 - Ibrahim harbi Ibrahim; Yasamine Hassan Said (Tikrit Journal For Political Science, 2023)
Achieving food security is one of the priority issues in various countries of the world، whether developed or developing. Therefore، specialized agricultural international organizations have given it a unique importance، and the United Nations has made its third development goal (the eradication of extreme poverty and hunger). Iraq is going through a critical period، which was manifested in the growing demand for agricultural and food products، in addition to the rise in food prices in the international markets and the diminishing relative importance of the agricultural sector in the Iraqi economic structure. The Iraqi agricultural output، as well as the deterioration of the percentage of agricultural area in the gross domestic product، led to the deterioration of the value of agricultural output، which led to a decline in the per capita share of this output .